Strategic Management of SIP (Assessment Information System) Applications to Improve Learning Outcomes - Detikurnia Detikurnia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
One way to improve the quality of human resources in educational institutions is through strategic management. This study aims to describe strategic management and the evaluation of the SIP (Assessment Information System) application in improving learning outcomes at SMA Negeri 1 Pangandaran. This study used qualitative methods, with the research subjects being the school operator and curriculum departments. The research was conducted at SMA Negeri 1 Pangandaran. Data collection techniques used in this study included observation, interviews, and documentation conducted directly in the field. Data analysis techniques used included data reduction, data presentation, and conclusion drawing. The results indicate that the strategic management of the SIP (Assessment Information System) application in improving learning outcomes is quite effective. The benchmarks for determining this management are three: goal achievement, integration, and adaptation. Achieving the goals of using the SIP application on learning outcomes at SMA Negeri 1 Pangandaran is an implementation of the institution's vision and mission. Furthermore, the integration process was also well-implemented and can be said to be quite effective in terms of socialization and communication between the parties involved. Furthermore, adaptation has also been quite successful, as SMA Negeri 1 Pangandaran has implemented the SIP application in stages, making it easier for everyone to adapt.